Pengaruh Pemberian Makanan Tambahan terhadap Penambahan Berat Badan Ibu Hamil dengan Kekurangan Energi Kronik - Rani Shiva Aulia; Demsa Simbolon; Yunita Yunita (FORIKES, 2023)
Supplementary feeding is nutritional supplementation in the form of layer biscuits made with a special formulation and fortified with vitamins and minerals for pregnant women, prioritizing the category of pregnant women with chronic energy deficiency to meet their nutritional needs. Chronic energy deficiency is a state of malnutrition that lasts a long time and is chronic, which can be caused by insufficient protein and energy intake in pregnant women. This study aimed to determine the effect of supplementary feeding on weight gain in chronic energy deficient pregnant women. The method used in this study was a systematic literature review, which was explained through a narrative. Articles taken from Google Scholar, PubMed, and ScienceDirect. The articles taken were articles published from 2010 to 2022, available in full text format, with a quasi-experimental design. The keywords used for the search were “supplementary feeding for pregnant women” AND “weight gain” AND “chronic energy deficiency”. Articles were collected using PRISMA diagrams and summarized into narratives. The results of the study showed that there were 9 identified articles. The results of the analysis stated that there was an effect of supplementary feeding on the weight gain of pregnant women with chronic energy deficiency, with the weight gain of pregnant women with chronic energy deficiency after supplementary feeding, as a whole in the articles obtained, namely 0.1 to 7 kg, with samples of pregnant women with chronic energy deficiency in the first, second and third trimesters. It was concluded that supplementary feeding was effective in increasing the body weight of pregnant women with chronic energy deficiency.Keywords: supplementary feeding; weight gain; pregnant mother; chronic energy deficiency ABSTRAK Pemberian makanan tambahan merupakan suplementasi gizi yang berupa biskuit lapis yang dibuat dengan formulasi khusus dan difortifikasi dengan vitamin dan mineral untuk ibu hamil, dengan memprioritaskan kategori ibu hamil dengan kekurangna energi kronik untuk mencukupi kebutuhan gizi. Kekurangan energi kronik merupakan keadaan malnutrisi yang berlangsung lama dan menahun, yang dapat disebabkan asupan protein dan energi yang kurang pada ibu hamil. Studi ini bertujuan untuk mengetahui pengaruh pemberian makanan tambahan terhadap penambahan berat badan ibu hamil kekurangan energi kronik. Metode yang yang digunakan dalam studi ini yaitu systematic literature review, yang dijelaskan melalui naratif. Artikel diambil dari Google Scholar, PubMed, dan ScienceDirect. Artikel yang diambil adalah artikel yang diterbitkan pada tahun 2010 sampai 2022, tersedia dalam format fulltext, dengan desain eksperimental kuasi. Kata kunci yang dipakai untuk pencarian adalah “pemberian makanan tambahan ibu hamil” AND “penambahan berat badan” AND “kekurangan energi kronik”. Artikel dikumpulkan dengan diagram PRISMA dan dirangkum menjadi narasi. Hasil studi menunjukkan bahwa terdapat 9 artikel yang teridentifikasi. Hasil analisis menyatakan bahwa ada pengaruh pemberian makanan tambahan terhadap penambahan berat badan ibu hamil dengan kekurangan energi kronik, dengan kenaikan berat badan ibu hamil dengan kekurangan energi kronik setelah pemberian makanan tambahan, secara keseluruhan pada artikel yang didapat yaitu 0,1 sampai 7 kg, dengan sampel ibu hamil dengan kekurangan energi kronik trimester I, II dan III. Disimpulkan bahwa pemberian makanan tambahan efektif untuk meningkatkan berat badan ibu hamil dengan kekurangan energi kronik.Kata kunci: pemberian makanan tambahan; penambahan berat badan; ibu hamil; kekurangan energi kronik